O zastosowaniu korelacji wielorakiej do ustalania regionalnych zasobów siły roboczej - Przedpelski, Mieczysław; Tarajkowski, Jerzy (Wydział Prawa i Administracji UAM, 1967)
The decision making with respect to an economic region requires a full knowledge of its labour potential resources. Hence the subject of this paper are the methods and some fragments of the results obtained in the process of evaluating the regional labour force resources with a simultaneous attempt to show and prove the possibility of using — in estimating them — the multicorrelation method, known in statistics (with a tacit assumption of a linear succession of resources in the long run). At the beginning the authors have given the definitions of potential and real labour force resources of a region, what in turn proved to be helpful in formulating the remarks concerning the premises on which the method of evaluating the resources is resting. The extrapolation of resources takes into consideration two points of depart: — extrapolation of prevailing tendency in resources, — extrapolation of factors determining the resources and next the computation of the resources themselves. For illustration purposes as well as for bringing into the relief the pecularities in the tendencies of examined resources — numerical examples relating to the whole of Poland and France have been given. In the estimation of the region's labour resources a method of multicorrelation can be used, in which the resources are circumscribed by factors known as essential. The acceptance of such a uniform method in many regions helps to get orientated in the size of labour resources in larger economic bodies.
On the multicorrelation method for the estimate of regional labour force resources